Examining the Relationship between Entrepreneurial Marketing and Business Performance: A Study on the E-commerce Industry in Egypt - Abdelsalam, Omar; Kortam, Wael (Archives of Business Research, 2023)
Information technology is considered to be one of the major contemporary forces pushing for globalisation, being an essential instrument for businesses supporting their tasks of strategic planning, cost control and overall business operations ( Laudon & Laudon, 2010). Since 2019, the world has been witnessing an upsurge with respect to internet usage and online shopping (Gohary, 2019). Consequently, the percentage of people engaging in e-commerce activities such as buying consumer goods, has been globally increasing by more than 8% reaching roughly 1.8 Billion people (Gohary, 2019). The disciplines of marketing and entrepreneurship have been perceived as two very distinguished ones from each other. The linkage between both disciplines is known by the name of “Entrepreneurial Marketing” (Rashad, 2018). The research utilized a quantitative approach in which data was collected from 123 respondents whom provided answers to an already reliable and validated scale and results were analysed statistically using the Statistical Package for Social Sciences (SPSS). Additionally, the research employed a qualitative approach with regards to data collected in which 5 In-depth semi-structured interviews were conducted with entrepreneurs and marketing managers of start-ups from within the E-commerce industry whom are responsible for the marketing decisions of their ventures. Results of the study showed that the different dimensions of entrepreneurial marketing proved to be related to business performance differently than one another, meaning that not all dimensions of entrepreneurial marketing are to be previewed as similar stimuli for either financial business performance of non-financial business performance